Real-world evaluation of select adverse drug reactions and healthcare utilization associated with parenteral Ibuprofen and ketorolac in adult and pediatric patients - Mosadoluwa Afolabi; Jensy Rodriguez-Silva; Ishveen Chopra; Ines Macias-Perez; Jason Makii; Emily Durr; Theresa Human (Frontiers in Pain Research)
IntroductionIntravenous non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used in healthcare settings, but their comparative safety and resource utilization impacts remain understudied. This study aimed to compare adverse drug reactions (ADRs) and healthcare resource utilization (HCRU) between patients receiving IV-ibuprofen versus IV/IM ketorolac.MethodsA retrospective, longitudinal analysis was conducted using an all-payer database, examining records from January 1, 2014, to June 3, 2023. The study included both adult (≥18 years) and pediatric (<18 years) populations who received one or more doses of either medication. Propensity score matching was applied to both populations, and HCRU was tracked for 29 days post-final dose. The adult cohort included 31,046 IV-ibuprofen and 124,184 ketorolac records, while the pediatric cohort had 5,579 patients per treatment arm.ResultsBoth adult and pediatric patients receiving IV-ibuprofen demonstrated lower ADR incidence and reduced HCRU compared to those receiving ketorolac.DiscussionThe findings suggest IV-ibuprofen may be a safer alternative to ketorolac, potentially improving patient care outcomes while reducing healthcare system burden. These results have implications for clinical practice and healthcare resource management.